Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation. Issue 1 (7th December 2022) - Ordóñez‐Parra, Carlos A.; Dayrell, Roberta L. C.; Negreiros, Daniel; Andrade, Antônio C. S.; Andrade, Letícia G.; Antonini, Yasmine; Barreto, Leilane C.; Barros, Fernanda de V.; Carvalho, Vanessa da Cruz; Corredor, Blanca Auxiliadora Dugarte; Davide, Antônio Cláudio; Duarte, Alexandre A.; et al.
Abstract: Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10, 187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications. Resumo: O avanço da ecologia funcional depende fundamentalmente da disponibilidade de dados sobre traços reprodutivos, incluindo dados de plantas tropicais, que têm sido historicamente subrepresentados em bancos de dados de traços funcionais globais. Embora alguns bancos de dados valiosos tenham sido criados recentemente, eles são restritos principalmente a áreas temperadas e a traços vegetativos, como traços de folhas e madeira. Neste artigo apresentamos Rock n' Seeds, um banco de dados de traços funcionais de sementes e experimentos de germinação de vegetações associadas a afloramentos rochosos do Brasil, os quais são reconhecidos como centros notáveis de diversidade e endemismo. Os dados foram compilados através de uma revisão sistemática na literatura, resultando em 103 publicações das quais foram extraídos os traços funcionais das sementes. O banco de dados inclui informações de 16 traços funcionais para 383 taxa de 148 gêneros, 50 famílias e 25 ordens. Estes dezesseis traços incluem dois traços de dispersão, seis de produção, quatro morfológicos, dois biofísicos e dois germinativos; os eixos principais do espectro ecológico da semente. O banco de dados também fornece os dados brutos para 48 experimentos de germinação para um total de 10.187 registros para 281 taxa. Os experimentos de germinação no banco de dados avaliaram o efeito de uma ampla gama de fatores abióticos e bióticos sobre a germinação e diferentes tratamentos de quebra de dormência. Particularmente, 8.255 desses registros incluem a contagem diária da germinação. Estas informações facilitarão a síntese de dados de germinação e a utilização deste banco de dados para uma grande variedade de questões ecológicas. Dada a variedade de traços das sementes e as amplas informações sobre germinação disponibilizadas por este banco de dados, esperamos que ele seja um recurso valioso para o avanço da ecologia funcional comparativa e para orientar a restauração baseada em sementes e a conservação da biodiversidade em ecossistemas tropicais megadiversos. Não há restrições de direitos autorais sobre os dados; favor citar este artigo ao utilizar os dados nas publicações e os autores agradeceriam uma notificação de como os dados são utilizados nas publicações. Resumen: El avance de la ecología funcional depende fundamentalmente de la disponibilidad de datos sobre rasgos reproductivos–incluyendo los de las plantas tropicales–los cuales han estado poco representados en las bases de datos globales de rasgos. Aunque recientemente se han creado algunas bases de datos valiosas, estas se encuentran restringidas principalmente a las zonas templadas y a los rasgos vegetativos, como los de las hojas y la madera. En este artículo presentamos Rock n' Seeds, una base de datos de rasgos funcionales de semillas y experimentos de germinación de la vegetación asociada a afloramientos rocosos de Brasil, los cuales son destacados centros de diversidad y endemismo. Los datos se recopilaron mediante una búsqueda bibliográfica sistemática, que dio como resultado 103 publicaciones de las que se extrajeron los rasgos funcionales de las semillas. La base de datos incluye información de dieciséis rasgos funcionales para 383 taxones de 148 géneros, 50 familias y 25 órdenes. Estos rasgos incluyen dos rasgos de dispersión, seis de producción, cuatro morfológicos, dos biofísicos y dos de germinación; siendo estos los principales ejes del espectro ecológico de las semillas. La base de datos también proporciona los datos brutos de 48 experimentos de germinación, para un total de 10.187 registros de 281 taxones. Dichos experimentos de germinación evaluaron el efecto de una amplia gama de factores abióticos y bióticos sobre la germinación y de diferentes tratamientos para romper la dormancia. En particular, 8.255 de estos registros cuentan con conteos diarios de germinación. Esto facilitará la síntesis de los datos de germinación y el uso de esta base de datos para una gran diversidad de preguntas ecológicas. Dada la variedad de rasgos de las semillas y la amplia información sobre germinación que ofrece esta base de datos, esperamos que sea un recurso valioso para el avance de la ecología funcional comparativa y para orientar la restauración basada en semillas y la conservación de la biodiversidad en ecosistemas tropicales megadiversos. No hay restricciones de derechos de autor sobre los datos; se solicita citar este documento cuando se utilicen los datos en publicaciones y los autores agradecerán ser notificados sobre cómo se utilizan los datos en las publicaciones.